RHO type structure molecular sieve containing metal cations as well as synthesis method and application of RHO type structure molecular sieve
Through guide agent-induced synthesis and ion exchange technology, the problem of expensive template agents and high energy consumption in RHO molecular sieve synthesis is solved, fast and low-cost production is achieved, and CO2 adsorption performance is improved.
Patent Information
- Application Number
- CN202411693774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2024-12-24
AI Technical Summary
The existing synthesis methods of RHO type molecular sieve are limited by expensive organic template agents and high temperature calcination, resulting in high production complexity and energy consumption, and inappropriate grain size, making it difficult to optimize industrial processes.
Na+, Cs-RHO molecular sieve was prepared by mixing silicon source, aluminum source, sodium source, cesium source and water, and introduced metal cations through ion exchange to achieve rapid crystallization and appropriate grain size. , reduce energy consumption and production costs.
The Na+, Cs-RHO molecular sieve with fast crystallization, low energy consumption and high efficiency production has a uniform grain size and excellent CO2 adsorption performance in the mixed gas of carbon dioxide, methane and nitrogen.
Smart Images

Figure CN119176566A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of molecular sieves, and in particular to a RHO type molecular sieve containing metal cations, a synthesis method and application thereof. Background Art
[0002] In recent years, the severe trend of global warming caused by excessive emissions of carbon dioxide (CO2) has become increasingly prominent, posing an unprecedented challenge to the ecological balance of the earth and the environment on which human beings depend for survival. Among the many response strategies, CO2 capture and separation technology has attracted much attention as an effective means to reduce emissions. This technical system covers a variety of methods such as solvent absorption, solid adsorption, membrane separation, and cryogenic fractionation.
[0003] Solid adsorption method stands out with its unique advantages. It uses the efficient and reversible adsorption capacity of solid adsorbents for CO2 in mixed gases to achieve effective separation and collection of CO2. This method not only has low energy consumption and simple operation, but also has significant characteristics such as large adsorption capacity, excellent cycle performance and non-corrosiveness, providing strong technical support for addressing climate change and promoting sustainable development. Molecular sieves have shown good performance in mixed gas adsorption separation and nitrogen oxide removal due to their unique pore structure, adjustable active sites and good hydrothermal stability.
[0004] RHO molecular sieve is a small-pore molecular sieve with a three-dimensional 8-membered ring pore structure of 3.6Å×3.6Å, and exhibits good performance in many catalytic reactions and adsorption separation processes. Chatelain et al. (Microporous Materials, 1995, 4, 231.) reported the synthesis of RHO molecular sieve by introducing organic 18-crown ether-6 as a template. Patent CN106799202A reports a method for synthesizing RHO molecular sieves with high silicon-aluminum ratio and adsorption characteristics, which has obvious advantages in gas adsorption selectivity and adsorption range. However, this synthesis method is not only limited by the high price of 18-crown ether-6, but also significantly increases the production complexity and energy consumption due to the subsequent high-temperature calcination to remove the organic template, thereby increasing the production cost of the molecular sieve. Mintova et al. (Chemistry of Materials, 2020, 32 (14): 5985-5993.) used a method without organic template to synthesize Na + ,Cs-RHO molecular sieve, whose molecular sieve crystal size is less than 100nm. The extremely small crystal size brings great difficulty to the solid-liquid separation process after crystallization, and puts forward higher requirements for subsequent process optimization. Therefore, a method for synthesizing RHO type molecular sieve adsorbent without template agent and with more suitable crystal size is currently needed. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a RHO-type structured molecular sieve containing metal cations and a synthesis method and application thereof. The synthesis method has a fast synthesis speed, a suitable grain size, and cheap and environmentally friendly raw materials; the RHO-type structured molecular sieve is applied to a mixed gas of carbon dioxide, nitrogen and / or methane to preferentially adsorb a large amount of carbon dioxide.
[0006] The present invention is achieved through the following technical solutions: On the one hand, a method for synthesizing a RHO-type molecular sieve containing metal cations is provided, and the method comprises the following steps: 1) Preparation of directing agent; The materials containing silicon source, aluminum source, sodium source, cesium source and water are fully mixed, stirred and aged to obtain a directing agent sol; then the directing agent sol is transferred to a reaction kettle for the first crystallization to obtain a directing agent; 2) Preparation of synthetic sol; The materials containing silicon source, aluminum source, sodium source and cesium source are mixed with water in a certain proportion, stirred evenly, and then a certain proportion of the above-mentioned directing agent is added for aging to obtain a synthetic sol; 3) After crystallization, drying and calcination, the synthesized sol is obtained. + ,Cs-RHO molecular sieve raw powder; 4) The obtained Na + , Cs-RHO molecular sieve powder is converted into NH4, Cs x -RHO molecular sieve, NH4 + ,Cs x -RHO molecular sieve is subjected to the second ion exchange to obtain M,Cs x -RHO molecular sieve; wherein x is molecular sieve Cs after (NH4)2SO4 solution exchange + Mass fraction; M is the Na in the metal cation + , K + Mg 2+ , Cu 2+ 、Zn 2+ and Fe 3+ One or more of.
[0007] Furthermore, in step 1), the added molar ratio of the silicon source, aluminum source, sodium source, cesium source and water is as follows: The molar ratio of SiO2 / Al2O3 is 5~15:1; The molar ratio of Na2O / Al2O3 is 4~12:1; The molar ratio of Cs2O / Al2O3 is 0.1~1:1; The molar ratio of H2O / Al2O3 is 20~100:1.
[0008] Furthermore, in step 1), the crystallization temperature of the first crystallization is 90° C. to 120° C., and the crystallization time is 2 h to 12 h.
[0009] Furthermore, in step 2), the molar ratio of the silicon source, aluminum source, sodium source, cesium source and water added is as follows: the molar ratio of SiO2:Al2O3:Na2O:Cs2O:H2O is 9~20:0.8~1.2:1~12:0.5~1.5:200~450.
[0010] Furthermore, in step 2), the amount of the directing agent added is 2.4wt%-10wt% of the total weight of SiO2 in the silicon source.
[0011] Furthermore, in step 2), the stirring temperature is 20° C. to 60° C., and the aging time is 4 h to 12 h.
[0012] Furthermore, in step 3), the crystallization temperature is 90° C. to 120° C., and the crystallization time is 2 h to 12 h.
[0013] Furthermore, in step 3), the drying temperature is 120°C, the drying time is 5h~10h, and the roasting temperature is 200~350°C.
[0014] Further, in step 4), the temperature of the first ion exchange is 40°C to 100°C, and the exchange time is 2 to 24 hours; or, the temperature of the second ion exchange is 60°C to 100°C, and the exchange time is 3 hours to 10 hours.
[0015] Furthermore, the silicon source is any one of white carbon black, silica sol and water glass, or a mixture of two or more of them in any proportion; Or the aluminum source is any one of pseudo-boehmite, aluminum sol, aluminum sulfate, sodium aluminate and boehmite, or a mixture of two or more of them synthesized in any proportion; Or the sodium source is sodium hydroxide; Alternatively, the cesium source is cesium hydroxide.
[0016] A method for synthesizing a RHO-type molecular sieve containing metal cations is also provided. x -RHO molecular sieve.
[0017] Finally, an application of the molecular sieve described above in selectively adsorbing and separating carbon dioxide from a mixed gas is provided.
[0018] Preferably, the mixed gas includes nitrogen and / or methane.
[0019] Beneficial Effects 1) The molecular sieve synthesis method provided by the present invention uses cheap raw materials and is environmentally friendly.
[0020] 2) This invention uses a directing agent to induce the synthesis of Na for the first time + ,Cs-RHO molecular sieve,Na + The crystallization time of Cs-RHO molecular sieve is short and the crystallization reaction can be completed within 12 hours, which improves industrial production efficiency and reduces energy consumption.
[0021] 3) This invention uses a directing agent to induce the synthesis of Na for the first time + ,Cs-RHO molecular sieve, can ensure the synthesis of Na + ,Cs-RHO type molecular sieve has a uniform and moderate grain size (500~700nm), which not only ensures high efficiency of production filtration, but also the smaller grain size is conducive to the rapid adsorption and desorption of small molecule gases.
[0022] 4) The cation-modified RHO molecular sieve adsorbent provided by the present invention can preferentially adsorb a large amount of carbon dioxide in a mixed gas of carbon dioxide, methane and nitrogen. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is Na described in Example 1 + , SEM image of Cs-RHO molecular sieve; Figure 2 It is Na described in Examples 1 to 9 + , XRD patterns of Cs-RHO and modified RHO molecular sieves; Figure 3 It is Na described in Example 4 7.5 + ,Cs 5.0 -RHO molecular sieve mixed gas adsorption isotherm diagram; DETAILED DESCRIPTION In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0024] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. The experimental methods without specific conditions in the following examples are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. Unless otherwise specified, all percentages, ratios, proportions or parts are by weight.
[0025] Unless otherwise specified, the reagents, raw materials and experimental instruments used in the examples and comparative examples of the present invention can be conventional raw materials and instruments obtained through commercial channels.
[0026] Example 1 10.8g of deionized water, 7.4g of sodium hydroxide, and 2.2g of cesium hydroxide were weighed and added in sequence, stirred evenly at room temperature, and a transparent solution was obtained after stirring for 30 minutes. 1.9g of sodium aluminate was added and stirred for 30 minutes to obtain a transparent solution. 18.8g of silica sol (mass fraction of SiO2 is 40%) was added and stirred evenly, and then aged at room temperature for 12 hours, and then crystallized at 90°C for 8 hours to obtain the final directing agent sol. In addition, 100.1g of deionized water, 8.5g of sodium hydroxide, and 4.4g of cesium hydroxide were weighed and added in sequence, stirred evenly at 40°C, and a transparent solution was obtained after stirring for 30 minutes. 3.82g of sodium aluminate was added and stirred for 30 minutes to obtain a transparent solution. 57.8g of water glass (mass fraction of SiO2 is 30.5%, mass fraction of Na2O is 8.2%) and 0.43g of directing agent were added and stirred evenly, and then aged at room temperature for 12 hours to obtain the final sol. Among them, the mass of SiO2 described in this embodiment is 17.6g, and the directing agent accounts for 2.4%.
[0027] The above sol was transferred to a reactor, and the reactor was heated to 100°C and kept for 12 hours to allow the mixed sol to complete the hydrothermal synthesis crystallization reaction. After the reaction was completed, the reactor was quickly cooled down, and the formed crystals were filtered and washed until the pH value of the washing liquid reached 7-9. The obtained solid product was dried at 120°C for 7 hours and then calcined at 300°C to obtain Na + ,Cs-RHO molecular sieve raw powder, SEM results, such as Figure 1 As shown, the XRD results show a RHO type structure, such as Figure 2 As shown in a.
[0028] Example 2 10.8g of deionized water, 7.4g of sodium hydroxide, and 2.2g of cesium hydroxide were weighed and added in sequence, stirred evenly at room temperature, and a transparent solution was obtained after stirring for 30 minutes. 1.9g of sodium aluminate was added and stirred for 30 minutes to obtain a transparent solution. 18.8g of silica sol (mass fraction of SiO2 is 40%) was added and stirred evenly, and then aged at room temperature for 12 hours, and then crystallized at 90°C for 8 hours to obtain the final directing agent sol. In addition, 100.1g of deionized water, 8.5g of sodium hydroxide, and 4.4g of cesium hydroxide were weighed and added in sequence, stirred evenly at 40°C, and a transparent solution was obtained after stirring for 30 minutes. 3.82g of sodium aluminate was added and stirred for 30 minutes to obtain a transparent solution. 57.8g of water glass (mass fraction of SiO2 is 30.5%, mass fraction of Na2O is 8.2%) and 1.23g of directing agent were added and stirred evenly, and then aged at room temperature for 12 hours to obtain the final sol. Among them, the mass of SiO2 described in this embodiment is 17.6g, and the directing agent accounts for 7.0%.
[0029] The above sol was transferred to a reactor, and the reactor was heated to 100°C and kept for 12 hours to allow the mixed sol to complete the hydrothermal synthesis crystallization reaction. After the reaction was completed, the reactor was quickly cooled down, and the formed crystals were filtered and washed until the pH value of the washing liquid reached 7-9. The obtained solid product was dried at 120°C for 7 hours and then calcined at 300°C to obtain Na + ,Cs-RHO molecular sieve raw powder, XRD results show RHO type structure, such as Figure 2 As shown in b.
[0030] Example 3 10.8g of deionized water, 7.4g of sodium hydroxide, and 2.2g of cesium hydroxide were weighed and added in sequence, stirred evenly at room temperature, and a transparent solution was obtained after stirring for 30 minutes. 1.9g of sodium aluminate was added and stirred for 30 minutes to obtain a transparent solution. 18.8g of silica sol (mass fraction of SiO2 is 40%) was added and stirred evenly, and then aged at room temperature for 12 hours, and then crystallized at 90°C for 8 hours to obtain the final directing agent sol. In addition, 100.1g of deionized water, 8.5g of sodium hydroxide, and 4.4g of cesium hydroxide were weighed and added in sequence, stirred evenly at 40°C, and a transparent solution was obtained after stirring for 30 minutes. 3.82g of sodium aluminate was added and stirred for 30 minutes to obtain a transparent solution. 57.8g of water glass (mass fraction of SiO2 is 30.5%, mass fraction of Na2O is 8.2%) and 1.76g of directing agent were added and stirred evenly, and then aged at room temperature for 12 hours to obtain the final sol. Among them, the mass of SiO2 described in this embodiment is 17.6g, and the directing agent accounts for 10.0%.
[0031] The above sol was transferred to a reactor, and the reactor was heated to 100°C and kept for 12 hours to allow the mixed sol to complete the hydrothermal synthesis crystallization reaction. After the reaction was completed, the reactor was quickly cooled down, and the formed crystals were filtered and washed until the pH value of the washing liquid reached 7-9. The obtained solid product was dried at 120°C for 7 hours and then calcined at 300°C to obtain Na + ,Cs-RHO molecular sieve raw powder, XRD results show RHO type structure, such as Figure 2 As shown in c.
[0032] Example 4 According to Example 1 + , the mass ratio of Cs-RHO molecular sieve sample to the volume ratio of ammonium sulfate solution (3 mol / L) S / L = 1g:30mL was stirred and mixed at 80℃ for 6h and filtered. After repeating this process 3 times, the obtained sample was washed with deionized water and dried at 100℃ for 12h to obtain NH4 + ,Cs 5.0 -RHO molecular sieve; NH4 + ,Cs 5.0 -RHO molecular sieve sample was stirred and mixed with 0.5 mol / L sodium chloride solution at 80°C for 6 h in a solid-liquid S / L ratio of 1 g:30 mL and then filtered. The obtained sample was washed with deionized water, dried at 100°C for 12 h, and then calcined in a muffle furnace at 550°C for 4 h to obtain Na 7.5 + ,Cs 5.0 -RHO molecular sieve, Na 7.5 + ,Cs 5.0 -RHO molecular sieve mixed gas adsorption isotherm diagram see Figure 3 As shown, Na 7.5 + ,Cs 5.0 -RHO molecular sieve XRD results show RHO type structure, such as Figure 2 As shown in d.
[0033] Example 5 According to Example 1 + , the mass ratio of Cs-RHO molecular sieve sample to the volume ratio of ammonium sulfate solution (3 mol / L) S / L = 1g:30mL was stirred and mixed at 80℃ for 6h and filtered. After repeating this process 3 times, the obtained sample was washed with deionized water and dried at 100℃ for 12h to obtain NH4 + ,Cs 5.0 -RHO molecular sieve; NH4 + ,Cs 5.0The -RHO molecular sieve sample was stirred and mixed with 0.5 mol / L potassium chloride solution at 80°C for 6 hours in a solid-liquid S / L ratio of 1g:30mL, and then filtered. The obtained sample was washed with deionized water, dried at 100°C for 12 hours, and then calcined in a muffle furnace at 550°C for 4 hours to obtain K 8.9 + ,Cs 5.0 -RHO molecular sieve, XRD results show RHO type structure, such as Figure 2 As shown in e.
[0034] Example 6 According to Example 1 + , the mass ratio of Cs-RHO molecular sieve sample to the volume ratio of ammonium sulfate solution (3 mol / L) S / L = 1g:30mL was stirred and mixed at 80℃ for 6h and filtered. After repeating this process 3 times, the obtained sample was washed with deionized water and dried at 100℃ for 12h to obtain NH4 + ,Cs 5.0 -RHO molecular sieve; NH4 + ,Cs 5.0 -RHO molecular sieve sample was stirred and mixed with 0.5 mol / L magnesium chloride solution at 80°C for 6 hours in a solid-liquid S / L ratio of 1g:30mL, and then filtered. The obtained sample was washed with deionized water, dried at 100°C for 12 hours, and then calcined in a muffle furnace at 550°C for 4 hours to obtain Mg 5.9 2+ ,Cs 5.0 -RHO molecular sieve, XRD results show RHO type structure, such as Figure 2 f.
[0035] Example 7 According to Example 1, Na + , the mass ratio of Cs-RHO molecular sieve sample to the volume ratio of ammonium sulfate solution (3 mol / L) S / L = 1g:30mL was stirred and mixed at 80℃ for 6h and filtered. After repeating this process 3 times, the obtained sample was washed with deionized water and dried at 100℃ for 12h to obtain NH4 + ,Cs 5.0 -RHO molecular sieve; NH4 + ,Cs 5.0 -RHO molecular sieve sample was stirred and mixed with 0.5 mol / L copper chloride solution at 80°C for 6 hours in a solid-liquid S / L ratio of 1g:30mL, and then filtered. The obtained sample was washed with deionized water, dried at 100°C for 12 hours, and then calcined in a muffle furnace at 550°C for 4 hours to obtain Cu 6.62+ ,Cs 5.0 -RHO molecular sieve, XRD results show RHO type structure, such as Figure 2 As shown in g.
[0036] Example 8 According to Example 1, Na + , the mass ratio of Cs-RHO molecular sieve sample to the volume ratio of ammonium sulfate solution (3 mol / L) S / L = 1g:30mL was stirred and mixed at 80℃ for 6h and filtered. After repeating this process 3 times, the obtained sample was washed with deionized water and dried at 100℃ for 12h to obtain NH4 + ,Cs 5.0 -RHO molecular sieve; NH4 + ,Cs 5.0 -RHO molecular sieve sample was stirred and mixed with 0.5 mol / L zinc chloride solution at 80°C for 6 h in a solid-liquid ratio of S / L=1g:30mL and then filtered. The obtained sample was washed with deionized water, dried at 100°C for 12 h, and then calcined in a muffle furnace at 550°C for 4 h to obtain Zn 6.5 2+ ,Cs 5.0 -RHO molecular sieve, XRD results show RHO type structure, such as Figure 2 h.
[0037] Example 9 According to the ratio of the mass of the Na,Cs-RHO molecular sieve sample to the volume of the ammonium sulfate solution (3 mol / L) as described in Example 1, the mixture was stirred and mixed at 80°C for 6 hours and filtered. This process was repeated 3 times, and the obtained sample was washed with deionized water and dried at 100°C for 12 hours to obtain NH4 + ,Cs 5.0 -RHO molecular sieve; NH4 + ,Cs 5.0 -RHO molecular sieve sample was stirred and mixed with 0.5 mol / L ferric chloride solution at 80°C for 6 h in a solid-liquid S / L ratio of 1 g:30 mL and then filtered. The obtained sample was washed with deionized water, dried at 100°C for 12 h, and then calcined in a muffle furnace at 550°C for 4 h to obtain Fe 5.8 3+ ,Cs 5.0 -RHO molecular sieve, XRD results show RHO type structure, such as Figure 2 As shown in i.
[0038] Comparative Example 1 According to Example 1, Na +The mass ratio of Cs-RHO molecular sieve sample to the volume ratio of ammonium sulfate solution (0.3 mol / L) S / L = 1g:30mL was stirred and mixed at 80℃ for 6h and filtered. After repeating this process once, the obtained sample was washed with deionized water, dried at 100℃ for 12h, and then placed in a muffle furnace and calcined at 550℃ for 4h to obtain Na 6.0 + ,Cs 22.0 -RHO molecular sieve.
[0039] Comparative Example 2 Weigh 95.3g of deionized water and 6.88g of sodium hydroxide, stir for 20 minutes to fully dissolve, and divide the solution into two beakers marked as solution A and solution B. Add 13.2g of sodium aluminate to solution A and stir for 20 minutes until the solution is clear. Add 23.3g of water glass to solution B and stir for 20 minutes until the solution is clear. Slowly pour solution B into solution A and stir for 10 minutes to form a sol. Seal the beaker and place it in an oven at 100°C. After the crystallization reaction is completed for 4 hours, filter and wash the formed crystals until the pH value of the washing liquid reaches 7-9. Dry the obtained solid product at 120°C for 7 hours and calcine at 300°C to obtain NaA molecular sieve raw powder. Wash the obtained sample with deionized water, dry it at 100°C for 12 hours, and then place it in a muffle furnace and calcine it at 550°C for 4 hours to obtain Na 4.8 A molecular sieve.
[0040] Comparative Example 3 According to the method described in CN111039303A, the silicon content is Si / (Si+Al+P) molar ratio = 0.145, the crystallization temperature is 200°C, the crystallization time is 72h, after the reaction is completed, the reactor is quickly cooled, filtered and washed until the pH value of the washing liquid reaches 7-9, the obtained crystals are stirred and mixed with 0.5mol / L lithium chloride solution at 80°C for 6h according to the ratio of solid-liquid S / L=1g:30mL, and then filtered, the obtained sample is washed with deionized water, dried at 100°C for 12h, and then placed in a muffle furnace and calcined at 550°C for 4h to obtain Li 5.8 -SAPO-RHO molecular sieve.
[0041] Comparative Example 4 According to the method in the literature (J Colloid Interface Sci, 2021, 582:90–101), activated carbon was prepared by carbonization and KOH activation using rice husk as raw material. The prepared activated carbon and chitosan were fully ground and mixed in a ratio of 1:1, and then the mixture was placed in a muffle furnace and calcined at 550°C for 4 hours to obtain N-AC adsorbent.
[0042] Effect Example 1 The RHO molecular sieve adsorbents prepared in Examples 1 to 9 and the sample adsorbents prepared in Comparative Examples 1 to 4 were subjected to a mixed gas selective adsorption and separation test. Before the test, all molecular sieve samples were activated at 350° C. for 6 h under vacuum conditions. After the samples were cooled to room temperature, single-component gas isothermal adsorption and desorption tests were performed. The test temperature was 25° C. and the test pressure was 0 to 1.0 bar. Table 1 below is the test data of Examples 1 to 9 and Comparative Examples 1 to 4 for CO2, CH4 and N2 at 25° C. and 1.0 bar.
[0043] Table 1
[0044] Through the above data analysis, it can be seen that: + , Cs-RHO molecular sieve has mild synthesis conditions, short crystallization time, and no need for organic template. After modification with different metal cations, the prepared modified M, Cs-RHO (M = Na + , K + Mg 2+ , Cu 2+ 、Zn 2+ and Fe 3+ ) molecular sieve adsorbents, especially Na + The modified RHO framework structure molecular sieve adsorbent exhibits excellent selective adsorption capacity for carbon dioxide, as well as adsorption and separation capabilities for carbon dioxide, methane and nitrogen.
[0045] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for synthesizing a RHO-type molecular sieve containing metal cations, characterized in that: The synthesis method comprises the following steps: 1) Preparation of directing agent; The materials containing silicon source, aluminum source, sodium source, cesium source and water are fully mixed, stirred and aged to obtain a directing agent sol; then the directing agent sol is transferred to a reaction kettle for the first crystallization to obtain a directing agent; 2) Preparation of synthetic sol; The materials containing silicon source, aluminum source, sodium source and cesium source are mixed with water in a certain proportion, stirred evenly, and then a certain proportion of the above-mentioned directing agent is added for aging to obtain a synthetic sol; 3) After crystallization, drying and calcination, the synthesized sol is obtained. + ,Cs-RHO molecular sieve raw powder; 4) The obtained Na + , Cs-RHO molecular sieve powder is converted into NH4 by the first ion exchange + ,Cs x -RHO molecular sieve, NH4 + ,Cs x -RHO molecular sieve is subjected to the second ion exchange to obtain M,Cs x -RHO molecular sieve; wherein x is molecular sieve Cs after (NH4)2SO4 solution exchange + Mass fraction; M is the Na in the metal cation + , K + Mg 2+ , Cu 2+ 、Zn 2+ and Fe 3+ One or more of.
2. The method for synthesizing a RHO-type molecular sieve containing metal cations according to claim 1, characterized in that: In step 1), the added molar ratio of the silicon source, aluminum source, sodium source, cesium source and water is as follows: The molar ratio of SiO2 / Al2O3 is 5~15:1; The molar ratio of Na2O / Al2O3 is 4~12:1; The molar ratio of Cs2O / Al2O3 is 0.1~1:1; The molar ratio of H2O / Al2O3 is 20~100:
1.
3. The method for synthesizing a RHO-type molecular sieve containing metal cations according to claim 1, characterized in that: In step 1), the crystallization temperature of the first crystallization is 90° C. to 120° C., and the crystallization time is 2 h to 12 h.
4. The method for synthesizing a RHO-type molecular sieve containing metal cations according to claim 1, characterized in that: In step 2), the molar ratio of the silicon source, aluminum source, sodium source, cesium source and water added is as follows: the molar ratio of SiO2:Al2O3:Na2O:Cs2O:H2O is 9~20:0.8~1.2:1~12:0.5~1.5:200~450.
5. The method for synthesizing a RHO-type molecular sieve containing metal cations according to claim 1, characterized in that: In step 2), the amount of the directing agent added is 2.4wt%-10wt% of the total weight of SiO2 in the silicon source; the stirring temperature is 20°C-60°C, and the aging time is 4h-12h.
6. The method for synthesizing a RHO-type molecular sieve containing metal cations according to claim 1, characterized in that: In step 3), the crystallization temperature is 90°C to 120°C, and the crystallization time is 2h to 12h; the drying temperature is 120°C, and the drying time is 5h to 10h; and the calcination temperature is 200°C to 350°C.
7. The method for synthesizing a RHO-type molecular sieve containing metal cations according to claim 1, characterized in that: In step 4), the temperature of the first ion exchange is 40°C to 100°C, and the exchange time is 2h to 24h; or, the temperature of the second ion exchange is 60°C to 100°C, and the exchange time is 3h to 10h.
8. The method for synthesizing a RHO-type molecular sieve containing metal cations according to claim 1, characterized in that: The silicon source is any one of white carbon black, silica sol and water glass, or a mixture of two or more of them in any proportion; Or the aluminum source is any one of pseudo-boehmite, aluminum sol, aluminum sulfate, sodium aluminate and boehmite, or a mixture of two or more of them synthesized in any proportion; Or the sodium source is sodium hydroxide; Alternatively, the cesium source is cesium hydroxide.
9. M, Cs prepared by the synthesis method of the RHO type molecular sieve containing metal cations according to any one of claims 1 to 8 x -RHO molecular sieve.
10. An application of the molecular sieve according to claim 9 in selectively adsorbing and separating carbon dioxide from mixed gases, characterized in that: The mixed gas includes nitrogen and / or methane.
Citation Information
Patent Citations
Method for preparing monodisperse regular-crystal-shape ZSM-5 molecular sieve by using template-free system
CN105836756A
Molecular sieve for gas separation, and preparation and application of molecular sieve
CN106799202A
Method for synthesizing molecular sieve structures by means of microwave reinforcement liquid phase regulation and control
CN109437229A
RHO zeolites and method of making the same
CN110961075A
Preparation method of ZSM-5 zeolite molecular sieve with low silica-alumina ratio
CN111547739A
